The Effect of the Group Investigation (GI) Teaching Model on Elementary Students’ Learning Outcomes in Thematic Learning - Alfateza, Rahma; Akbarjono, Ali; Nurhikma, Nurhikma (Jurnal Indonesia Pendidikan Profesi Guru, 2025)
Background: In response to the growing need for student-centered learning approaches in elementary education, the Group Investigation (GI) model offers a collaborative framework that encourages active participation, critical thinking, and meaningful learning. Thematic learning, which integrates multiple subjects around a central theme, benefits from such interactive models that foster deeper understanding and engagement. Objective: This study examines the impact of the Group Investigation (GI) learning model on students' learning outcomes in thematic learning at SD IT UMMI Kota Bengkulu. Method: Using a quantitative experimental approach with a nonequivalent group posttest design, this research compares students' learning outcomes between an experimental class (applying the GI model) and a control class (using conventional methods) through pretests and posttests. Results: The GI model had a significant effect on students' learning outcomes. The mean score of the experimental class (0.46) was higher than that of the control class (0.35), with a confidence interval of the difference ranging from 0.10 to 18.77 at a 5% significance level. This indicates an average learning outcome improvement of 0.10. Conclusion: The GI model is effective in enhancing conceptual understanding, social interaction, collaboration, and critical thinking skills among students. Contribution: This study contributes by recommending the GI model as an innovative teaching strategy and serving as a reference for future research on collaborative learning methods.